Pilot Study to Enhance Cover-Selection-Based Audio Steganography (CAS) Using Feed-Forward Neural Network - Taqiyuddin Anas; Farida Hazwani Mohd Ridzuan; Sakinah Ali Pitchay (UiTM Press, Universiti Teknologi MARA, 2025)
Indexed Publication (Tier 3)